Functionalization of Chitosan with Maleic Anhydride for Proton Exchange Membrane - Muhammad Ridwan Septiawan; Dian Permana; Sitti Hadijah Sabarwati; La Ode Ahmad; La Ode Ahmad Nur Ramadhan (Universitas Gadjah Mada, 2018)
Chitosan was modified by maleic anhydride, and it was then functionalized using heterogeneous and blending method to obtain the membrane. The results of the reaction between chitosan with maleic anhydride were signed by the new peak appears around 1475 cm-1 which attributed to C=C bending of alkene. The new peak also appears at 1590 cm-1 which attributed to N-H bending of amide. Chitosan-maleic anhydride membranes show microstructure of chitosan membrane with high porous density and rigidity while chitosan-maleic anhydride membranes have clusters. In addition, the thermal tenacity of membranes reached 500 °C. Modified membrane by heterogeneous and blending method have higher water uptake, ion exchange capacity, and proton conductivity than chitosan membrane. Moreover, the blending method is much more effective than the heterogeneous method that can be exhibited from ion exchange capacity and proton conductivity values of 1.08–6.38 meq g-1 and 1x10-3–1x10-2 S cm-1, 0.92–2.27 meq g-1 and 1.53x10-4–3.04x10-3 S cm-1, respectively. The results imply that modification of chitosan membrane with the addition of maleic anhydride using heterogeneous and blending method can be applied to proton exchange membrane.